Export promotion programmes and SMEs' performance: Exploring the network promotion role. Issue 1 (20th February 2017) - Haddoud, Mohamed Yacine; Jones, Paul; Newbery, Robert
Abstract : Purpose: The purpose of this paper is to investigate the network promotion role of export promotion programmes in driving small and medium enterprises' (SMEs) export performance. Design/methodology/approach: Drawing on a dual institutional and network-based approaches to internationalisation, the study tests an integrative model that explores the mediating role of SMEs' relationships in the link between government export promotion programmes (both informational and experiential forms) and export performance. The model was tested using a sample of 160 UK small and medium exporter firms. The data were analysed through a structural equation modelling technique. Findings: The study finds that whilst both informational and experiential export promotion programmes improved all forms of SMEs' relationships, only experiential forms had an indirect effect on export performance. Further, only relationships with foreign buyers had a positive impact on export performance. Research limitations/implications: The results of this research provide directions for export promotion organisations in targeting their network support provision and for SMEs in utilising such a support. The study calls for similar research in different contexts to validate the proposed model. Originality/value: This study brings novel findings to the extant literature by conceptualising and validating the importance of the "network promotion" element of export promotion programmes.